Bandwidth and Gain Enhancement of a Modified Ultra-wideband (UWB) Micro-strip Patch Antenna using a Reflecting Layer - Bari, Bifta Sama; Sabira, Khatun; Kamarul Hawari, Ghazali; Fakir, Md. Moslemuddin; Mohd Hisyam, Mohd Ariff; Mohd Faizal, Jamlos; Rashid, Mamunur; Islam, Minarul; M. Z., Ibrahim; Mohd Falfazli, Mat Jusof (Universiti Malaysia Pahang, 2019)
A novel technique to enhance bandwidth and gain of an Ultra-Wideband (UWB) antenna using a reflecting layer is presented in this chapter. A Microstrip Patch Antenna (MPA) with T-shaped patch and partially grounded plane is used in this design where a T-slot is inserted into the patch. The pro-posed compact-size antenna is designed and simulated using Computer Simula-tion Technology (CST) Microwave Studio software by considering flame retar-dant 4 (FR-4) as substrate with a relative permittivity of 4.3 and a thickness 1.6 mm. The antenna efficiency includes, a wide impedance bandwidth of 9.31 GHz ranging from 3.19 GHz to 12.5 GHz, for voltage standing wave ratio, VSWR<2; 5.74 dB gain; and 6.87 dBi directivity. In comparison with the MPA without the reflecting layer, the bandwidth, gain and directivity of the proposed antenna (with reflector) is increased by 123%, 3.64 dB, and 3.44 dBi respec-tively. Thus, the proposed antenna can cover a wider range than the UWB range (3.1-10.6 GHz) and can be suitable for the use of various bio-medical applications.